The Use of Reading Strategies in EFL Leaning - Eva Meidi Kulsum; Ervan Fauzan; Rina Mutiarawati (UIN Sunan Gunung Djati Bandung, 2023)
This research examined the use of reading strategies to the students who learned English as a Foreign Language (EFL) reading in an English dormitory. It employed qualitative descriptive method by distributing questionnaires and taking a transcript of interview. The questionnaire used in this study was Reading Strategies Questionnaire (RSQ) adopted from R. Oxford et al. (2004). Based on the questionnaire and interview session, it was found that students mostly relied on top-down reading strategies (55.38%) they also considered bottom-up reading strategies were beneficial for their reading comprehension (44.62%) since they used both strategies simultaneously when they were reading a text. From the result of this study, it is inferred that the effectiveness of the use of a certain strategy does not depend on the strategy itself, what makes a strategy effective is associated with how it is employed. Therefore, teaching on how to use reading strategies is useful to improve students’ comprehension since effective strategies can be taught and reading comprehension can be improved through instruction.